2016
DOI: 10.1590/1980-5497201600040010
|View full text |Cite
|
Sign up to set email alerts
|

Transmissão da doença de Chagas por consumo de carne de caça: revisão sistemática

Abstract: ABSTRACT:Objective: To evaluate the influence of game meat consumption in Chagas disease (CD) transmission, the conditions under which it occurs and the frequency of reports in the literature. Methods: Through systematic review, databases PubMed, LILACS, MEDLINE, and SciELO were consulted, and articles written in Portuguese, English, and Spanish were included, with no limitation over publication date. We used the following descriptors: oral, transmission, meat, wild animals, hunt, carnivory, and Chagas disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
10
1
10
Order By: Relevance
“…Factors associated with the hunting, sacrifice and manipulation of these animal species could represent a potential risk for accidental contamination with T. cruzi in humans. Of particular importance, several species from the order Cingulata (popularly known armadillos and cachicamos) and from the order Chiroptera (bats) are believed to have curative properties in some communities; for this reason their blood is consumed immediately after sacrifice as part of curative rituals, a practice described even from the pre-Columbian era [74, 75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with the hunting, sacrifice and manipulation of these animal species could represent a potential risk for accidental contamination with T. cruzi in humans. Of particular importance, several species from the order Cingulata (popularly known armadillos and cachicamos) and from the order Chiroptera (bats) are believed to have curative properties in some communities; for this reason their blood is consumed immediately after sacrifice as part of curative rituals, a practice described even from the pre-Columbian era [74, 75].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an important limitation is related to diagnostic methods. An important recent study in triatomine vectors has identified that optical microscopy used for routine surveillance missed ~50–75% of infections and wrongly scored as infected ~7% of the bugs when only one slide per vector was used [75]. For animals, we found the use of various tests with high specificity for T. cruzi detection such as xenodiagnostic, haemoculture and coloured smears, and in the case of the family Canidae serological methods were used and in some cases with PCR confirmation [76, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Oral transmission involving mammalian stage parasites (BTs and amastigotes) is rarely studied. A few cases of acute infection linked to consumption of infected meat from animal reservoirs have been reported 36 and carnivory is a component of sylvatic transmission cycles 37 . In our experiments, BTs were not transmissible via the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar dos esforços promovidos pela Organização Mundial da Saúde-OMS, numa abordagem denominada One Health, "para projetar e implementar programas, políticas, legislação e pesquisa nas quais vários setores se comunicam e trabalham juntos para alcançar melhores resultados de saúde pública" (WHO, 2017), ainda não há reconhecimento suficiente de que a nossa saúde está intimamente ligada à sustentabilidade e à saúde dos ecossistemas. O desmatamento, a fragmentação e a conversão dos ecossistemas naturais, o crescimento urbano desordenado e, de uma forma ainda mais direta, práticas como a caça e a venda de animais silvestres para consumo humano, são consideradas as principais causas de propagação de doenças zoonóticas (DOBSON et al, 2020;SANGENIS, 2016;ALHO, 2012;JORGE et al, 2010).…”
Section: Parques Saudáveis Pessoas Saudáveisunclassified